Perencanaan Pengembangan Desa Perempuan Indonesia Maju Mandiri di Daerah Istimewa Yogyakarta - Kuntarta, Kuntarta (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2020)
This research aimed to determine the development planning of the Advanced Indonesian Women's Village (Desa PRIMA) in Yogyakarta Special Region. The results showed that the development planning of the Advanced Indonesian Women's Village (Desa PRIMA) in Yogyakarta Special Region had been trapped in routine for all this time. The planning that were carried out were only repetitive from year to year and all target villages received the same treatment. This condition was due to the lack of profile data of the Advanced Indonesian Women's Village (Desa PRIMA), whereas in planning, problems must be based on data. For the development aspect of of the Advanced Indonesian Women's Village (Desa PRIMA), maximum efforts had been done on the capital and management aspects. Unfortunately, marketing, technology and innovation aspects had not been optimally implemented.